Bone metabolism markers and bone mineral density in children with neurofibromatosis type-1 - Duman, Ozgur; Ozdem, Sebahat; Turkkahraman, Doga; Olgac, Nihal Dundar; Gungor, Firat; Haspolat, Senay (Brain & development, 2008)
Some experimental studies suggested that there may be a bone formation defect rather than a disorder in bone resorption in patients NF1. The aim of this study was to determine bone mineral density (BMD) with dual-energy X-ray absorptiometry (DEXA) and investigate specific bone formation and bone resorption and bone turnover markers in children with NF1. Thirty-two children and adolescents (16 boys, 16 girls; 16 prepubertal, 16 pubertal) with NF1 were recruited. Their age ranged from 3 to 17 years. They were compared with matched healthy children. Dual-energy X-ray absorptiometry were applied to 26 patients and 27 controls. Nine of 32 subjects with NF1 had a skeletal abnormality. BMD of the lumbar spine, and femoral neck in NF1 patients significantly decreased compared to that of healthy subjects. They were also significantly decreased in pubertal patients when compared to pubertal controls and in prepubertal patients when compared to prepubertal controls. Patients with skeletal abnormalities were found to have significantly lower level of osteocalcin when compared to patients without skeletal abnormality. Other biochemical markers did not exhibit any difference between the groups. In conclusion, our findings suggest that bone formation markers rather than DEXA could be good predictors of skeletal abnormalities among NF1 patients. However, in our study the number of the NF1 patients with skeletal abnormality and the number of bone formation markers studied were all limited. It is appropriate to perform larger studies with other bone formation markers beside osteocalcin.